Immune checkpoint inhibitors associated cardiovascular immune-related adverse events - Jo, Wonyoung; Won, Taejoon; Daoud, Abdel; Čiháková, Daniela (Frontiers in Immunology, 2024)
Immune checkpoint inhibitors (ICIs) are specialized monoclonal antibodies (mAbs) that target immune checkpoints and their ligands, counteracting cancer cell-induced T-cell suppression. Approved ICIs like cytotoxic T-lymphocyte antigen-4 (CTLA-4), programmed death-1 (PD-1), its ligand PD-L1, and lymphocyte activation gene-3 (LAG-3) have improved cancer patient outcomes by enhancing anti-tumor responses. However, some patients are unresponsive, and others experience immune-related adverse events (irAEs), affecting organs like the lung, liver, intestine, skin and now the cardiovascular system. These cardiac irAEs include conditions like myocarditis, atherosclerosis, pericarditis, arrhythmias, and cardiomyopathy. Ongoing clinical trials investigate promising alternative co-inhibitory receptor targets, including T cell immunoglobulin and mucin domain-containing protein 3 (Tim-3) and T cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT). This review delves into the mechanisms of approved ICIs (CTLA-4, PD-1, PD-L1, and LAG-3) and upcoming options like Tim-3 and TIGIT. It explores the use of ICIs in cancer treatment, supported by both preclinical and clinical data. Additionally, it examines the mechanisms behind cardiac toxic irAEs, focusing on ICI-associated myocarditis and atherosclerosis. These insights are vital as ICIs continue to revolutionize cancer therapy, offering hope to patients, while also necessitating careful monitoring and management of potential side effects, including emerging cardiac complications.